Organogels for intratumoural delivery - Mohamed, Masar Basim Mohsin (2017)
The importance of localised delivery of chemotherapeutic drugs for cancer treatment and specifically solid tumours has been widely reported. In this study, the anticancer drug N4-myristoyl gemcitabine (a lipophilic form of gemcitabine) was formulated as organogel to achieve a localised depot delivery. Thus, the first goal of this study was to evaluate the suitability of the oragnogel for intartumoural injection and this attained by investigating the thermostability and elasticity of the organogel. Further to this, the second goal was to slow the release of N4-myristoyl gemcitabine from the organogel. Accomplishment of these two goals will guarantee a better efficacy of cancer treatment by obtaining direct contact of the organogel containing the N4-myristoyl gemcitabine with the cancerous cells. The studies herein selected the 12-hydroxystearic acid (12-HSA) as the gelator and using 2 types of solvents the liquid part of the organogel. The first type of solvent was a series of oils which were soybean oil (SO), medium chain triglyceride (MCT), glyceryl tributyrate (TGB) and glyceryl triacetate (GTA) whilst, the second type of solvent was propylene glycol (PG). Initially thermal stability was screened using table top rheology and DSC from 0.5% to 5% w/w 12-HSA in different oils. Also to test the mechanical strength of the organogels, amplitude sweep, frequency sweep, time dependant recovery and creep and recovery tests were executed to differentiate between the organogels. The best organogels were the 5% w/w 12-HSA in SO and MCT due to their highest thermal stability, denser scaffolds, thixotropic behaviour and were the least compliant. The same experiments were utilised to evaluate the selected range of 0.5% to 14% w/w 12-HSA in PG. 14% w/w 12-HSA in PG was selected again due to its higher thermal stability, thixotropic behaviour and was less compliant compared to other concentrations of 12-HSA in PG. Drug release from the selected organogels was then carried out. The cumulative percentage released from 0.5% and 0.3% w/w N4-myristoyl gemcitabine in 5% w/w 12-HSA/MCT organogels as a solid organogel was 18.95% and 26.62% after 30 days whilst for the organogel liquefied with N-methyl pyrrolidone (NMP), the cumulative percentage released was 35.02% and 34.37% within the same frame time. Further to this, a sample and separate release method was used to study the liquefied form of the 5% w/w 12-HSA/MCT. Also, this method revealed that the 5% w/w 12-HSA/MCT organogels gave a slow release of N4-myristoyl gemcitabine and 56.18% and 70.07% was released from the 0.5% and 0.3% w/w selected organogels respectively within 30 days. For the 14% w/w 12-HSA in PG organogel, the cumulative percentage released for 0.5% and 0.3% w/w N4-myristoyl gemcitabine in 14% w/w 12-HSA/PG organogels was 26% and 40% respectively after 30 days. To conclude, our selected organogels (5% w/w 12-HSA/MCT and 14% w/w 12-HSA/PG) met the goal of our work firstly, by showing the strength and the elasticity to be injected. Secondly, they were able to slow down the release of N4-myristoyl gemcitabine.